A dual-targeting bio-liposomes nanodrug repair endothelial cell dysfunction and restore macrophage cholesterol flow homeostasis to treat early atherosclerosis - Qi Zhang; Shengchao Ma; Xue Kang; Yi Liu; Fei Ma; Feifei Yu; Xiaolan Luo; Guizhong Li; Yinju Hao; Huiping Zhang; Bin Liu; Yideng Jiang (Journal of Nanobiotechnology)
Abstract Hyperhomocysteinemia (HHy) can lead to vascular endothelial cell dysfunction, progressive inflammation and lipid metabolism disorder, which finally result in the onset and development of atherosclerosis, a major contributor to cardiovascular diseases. Given the complexity of pathological process, treatments based on a single target often showed limited therapeutic efficacy against AS. Thus, developing nanodrug for enhanced multi-targets therapy is promising. In this study, we constructed a dual-targeting nanodrug (HA-ML@ES NPs) co-loaded with Shikonin (SKN) and Evolocumab (Evol). In vitro results showed that HA-ML@ES NPs could simultaneously target dysfunctional endothelial cell and inflammatory macrophage through the interaction between HA and CD44. In vivo assay indicated that HA-ML@ES NPs with long circulation and plaque accumulation efficiently attenuate endothelial cell dysfunction by inhibiting glycolysis and restore cholesterol flow homeostasis in macrophage by reprogramming macrophage phenotype, which finally attenuated the development of atherosclerosis. Collectively, these results present a highly promising dual-cell therapeutic approach based on HA-ML@ES NPs for the management of early atherosclerosis.